33rd Brazilian Society for Virology (SBV) 2022 Annual Meeting - Vaslin, Maite Freitas Silva; da Silva, Gustavo Peixoto Duarte; Leal, Alessandra Alevato; Bueno, Larissa Mayumi; Bittar, Cíntia [UNESP]; de Souza, Gabriela Fabiano; Lourenço, Karine [UNESP]; Guedes, Maria Isabel Maldonado Coelho; Proença-Módena, José Luiz; Araújo Júnior, João Pessoa [UNESP]; Ferreira, Helena Lage; da Fonseca, Flávio Guimarães (MDPI, 2023)
Each year, the Brazilian Society for Virology promotes a national meeting during the second semester of the year. In October 2022, the 33rd meeting took place at Arraial da Ajuda, Porto Seguro, Bahia, in-person:.this was the first in-person meeting since 2019, as the 2020 and 2021 events occurred online due to the issues imposed by COVID-19. It was a great pleasure for the whole audience to return to an in-person event, which certainly improved the interactions between the attendees in all ways. As usual, the meeting involved massive participation of undergraduate, graduate, and postdoc students, and several noteworthy international researchers were present. During five afternoons and evenings, attendees could discuss and learn about the most recent data presented by distinguished scientists from Brazil and other countries. In addition, young virology researchers from all levels could present their latest results as oral presentations and posters. The meeting covered all virology areas, with conferences and roundtables about human, veterinary, fundamental, environmental, invertebrate, and plant virology. The costs associated with attending the in-person event caused a slight reduction in the number of attendees compared to the two online events. However, even with this issue, the attendance was impressive. The meeting successfully achieved its most important goals: inspiring young and senior scientists and discussing high-quality, up-to-date virology research.
Keywords: basic virology; Brazilian Society for Virology; environmental virology; human virology; invertebrate virology; plant virology; SBV; SBV annual meeting; veterinary virology